Optimalisasi Peralatan Tambang dengan Metoda Overall Equipment Effectiveness (OEE) untuk Memenuhi Target Produksi Pengupasan Overbuden Bulan Agustus 2019 di Pit 1 Utara Bangko Barat PT. Satria Bahana Sarana Tanjung Enim Sumatera Selatan - Satria Rija1; Yoszi Mingsi Anaperta (Journals Mining Engineering : Bina Tambang, 2020)
Abstract. PT. Satria Bahana Sarana is a contracting company engaged in coal mining services located in Bangko Barat, Muara Enim Regency, South Sumatra Province. In August 2019, the overburden stripping production target was 1,095,000 bcm in which the realization of field production was 645,755 bcm which reached 59%. In the production calculation using the overall equipment effectiveness (OEE) method, the production value of 643,701.33 bcm is obtained with the effectiveness of each fleet of 34%, 44%, and 42% which have not reached the world OEE standard of 85%. Some of the causes of unattainable production targets are due to the many loss time in mechanical equipment that includes several factors such as system factors, human environment, and equipment. After making improvements to the loss time, a production calculation using the overall equipment effectiveness (OEE) method was found to increase production value to 1.097.696 bcm which met the overburden stripping production target in North Pit 1 in August of 1,095,000 bcm. And the effectiveness of mechanical equipment increased to 53%, 57%, and 44%.Keywords: Production, Loss Time, Overall Equipment Effectiveness, Excavator, Analysis Simple Linear Regression